A Novel Chemical -Microbial Hybrid Pesticide In The Management Of S.Oryzae L. - S.M. VIJILA,; S. SAM MANOHAR DAS,; R. RAJA JEYA SEKAR, (International Journal of Pharma and Bio Sciences, 2011)
Mortality of rice weevil, Sitophilus oryzae (L.) caused by Metarhizium anisopliae (Metschnikoff) Sorokin alone and in combination with a neonicotinoid insecticide, acetamiprid was evaluated in laboratory bioassays. Spray application of M. anisopliae alone at a spore concentration of 6 x 107 conidia/ml required 6 days to cause 10 percent mortality whereas 4 x 107 conidia/ml required 8 days to cause 10 percent mortality. Acetamiprid alone at a concentration of 30.00 µg/dl required 96h to cause 10% mortality and at 20.00 µg/dl required 120 h to cause 20% mortality. In combination with acetamiprid, M. anisopliae killed S.oryzae significantly faster than without acetamiprid. M. anisopliae at a spore concentration of 3 x 107 conidia/ml with 7.50 µg/dl acetamiprid killed 100 percent of the S. oryzae in 96 h and at 2 x 107 conidia/ml with 5.00 µg/dl acetamiprid killed 100 percent in 120 h. S. oryzae, M. anisopliae - acetomiprid combination resulted in higher mortality. Statistical analysis demonstrated synergistic interaction between these two insecticides.